Strategi Pemasaran Dakwah melalui Media Digital dalam Menarik Minat Masyarakat Belajar Agama Islam - Kurniawan, Rhohis; Castrawijaya, Cecep (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2025)
Digital transformation has presented great challenges and opportunities in the spread of Islamic da'wah, especially in reaching the millennial and Z generations who are very active in the digital world. The urgency of this topic lies in the need for a da'wah strategy that is adaptive and relevant to technological developments and the information consumption behavior of modern society. This research aims to examine the marketing strategy of da'wah through digital media in attracting people to study Islam. The method used is a descriptive qualitative approach with data collection techniques based on library research, as well as content analysis of relevant literature and academic documentation. The results of the study show that effective digital da'wah marketing strategies include audience segmentation, edutainment-based content development, strategic use of social media platforms, and technology-based learning personalization. Digital media is proven to increase accessibility, interactivity, and audience engagement in Islamic learning. This study concludes that structured and innovative digital da'wah can expand the reach of Islamic propagation while strengthening the spiritual understanding of modern society. Further studies are recommended to explore the effectiveness of specific platforms through empirical approaches and direct engagement with users.